Collaborative Governance in the Development of Culinary MSMEs - Kikin Oktavinia; Ginung Pratidina; Afmi Apriliani; Mulyadi; Mohd Nor Syahizan Ali (Administratie: Jurnal Administrasi Publik, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in creating local products and driving regional economic growth. The Government of Bogor Regency promotes the development of local products, particularly in the culinary sector. However, its implementation faces complex challenges among stakeholders, making collaboration an effective solution. One such initiative is a partnership program between the Department of Cooperatives and MSMEs (DISKOPUKM) and PT Indomarco Prismatama, the operator of Indomaret. This study aims to examine how collaboration operates within this partnership program, as well as to identify the challenges and efforts during the collaborative process. A descriptive quantitative method was employed, involving 32 respondents consisting of DISKOPUKM employees and MSME partners of Indomaret. The samples were selected using saturated and purposive sampling techniques. Data were collected through questionnaires, observation, interviews, and literature review. The results indicate that collaborative governance has been effectively implemented, with all dimensions well applied, as reflected by an average score of 4.24 (employees) and 4.12 (MSMEs). The highest dimension for employees is Collaborative Dynamics, reflecting effective communication and coordination, while for MSMEs it is Collaborative Actions and Outcomes, indicating tangible benefits. The lowest dimensions Drivers (employees) and Collaborative Dynamics (MSMEs) suggest the presence of uncertainty, communication barriers, and capacity gaps.The main challenges identified include issues in communication and coordination, suboptimal leadership, dependency on certain actors, and inconsistency among MSMEs in maintaining partnerships. Therefore, strengthening communication and coordination, enhancing leadership in collaboration, and establishing regular monitoring and evaluation mechanisms on a monthly basis are necessary to ensure measurable and sustainable outcomes of the collaboration program.